Polymorphism of ADIPOQ and EDG1 genes in Indonesian beef cattle - Sutikno, S.; Priyanto, R.; Sumantri, C.; Jakaria, J. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The ADIPOQ and EDG1 genes were responsible in intramuscular fat deposition and marbling scores. This study was aimed to identify polymorphism of indel g.81966364D>I in promoter region of ADIPOQ gene and SNP c.-312A>G in 5' UTR of EDG1 gene in Indonesian beef cattle. Blood samples were collected from 211 cattle, including Bali (44), Madura (20), Pesisir (18), Katingan (20), PO (22), Pasundan (20), SO (12), Brahman (20), Simmental (15) and Limousin (18). Polymorphism of ADIPOQ gene was analyzed using PCR and direct sequencingmethods, whereas EDG1 gene was analyzed using PCR-RFLP (MscI enzyme) and direct sequencingmethods. Results of genotyping indel g.81966364D>I was monomorphic (DD genotype). The SNP c.-312A>G was polymorphic (AA and AG genotype) in Madura, Pesisir, Pasundan, Brahman, and Limousine. The Frequencies of allele A and G were 0.95, 0.92, 0.98, 0.95, 0.94 and 0.05, 0.08, 0.02, 0.05, 0.06 respectively. The values of Ho and He were 0.05-0.17 and 0.05-0.15 respectively and in Hardy-Weinberg equilibrium (P>0.05). In Bali, Katingan, PO, SO and Simmental were monomorphic (GG genotype). In Bali cattle, two novel SNP candidates were found in position of c.-399C>T and c.-273C>G which were potential to be used as genetic markers of marbling score for Bali cattle. As result this study, it can be concluded that ADIPOQ gene was similar while EDG1 gene was different in Indonesian beef cattle. in addition, found two candidates potential SNP in Bali cattle.